Educating and advocating: A professional responsibility for school leaders and school counselors - Jessica Lane; Donna Augustine-Shaw; Melanie Scott (The Advocate, 2022)
While educators are tasked with many competing professional responsibilities, it is necessary that the focus of advocacy for student well-being stay at the forefront. In particular, for school counselors and school leaders, advocating has never been more important. This article will highlight the role of advocacy found within the professional standards for school counselors and school leaders, and shine light on the need to advocate for social-emotional learning.
Keywords: educate; advocacy; leadership; school leaders; school counselors; social-emotional learning